Integrative analysis of a phase 2 trial combining lenalidomide with CHOP in angioimmunoblastic T-cell lymphoma - Lemonnier, François; Safar, Violaine; Beldi-Ferchiou, Asma; Cottereau, Anne-Ségolène; Bachy, Emmanuel; Cartron, Guillaume; Fataccioli, Virginie; Pelletier, Laura; Robe, Cyrielle; Letourneau, Audrey; Missiaglia, Edoardo; Fourati, Slim; et al. (Blood advances, 2021)
Angioimmunoblastic T-cell lymphoma (AITL) is a frequent T-cell lymphoma in the elderly population that has a poor prognosis when treated with cyclophosphamide, doxorubicin, vincristine, and prednisone  (CHOP) therapy. Lenalidomide, which has been safely combined with CHOP to treat B-cell lymphoma, has shown efficacy as a single agent in AITL treatment. We performed a multicentric phase 2 trial combining 25 mg lenalidomide daily for 14 days per cycle with 8 cycles of CHOP21 in previously untreated AITL patients aged 60 to 80 years. The primary objective was the complete metabolic response (CMR) rate at the end of treatment. Seventy-eight of the 80 patients enrolled were included in the efficacy and safety analysis. CMR was achieved in 32 (41%; 95% confidence interval [CI], 30%-52.7%) patients, which was below the prespecified CMR rate of 55% defined as success in the study. The 2-year progression-free survival (PFS) was 42.1% (95% CI, 30.9%-52.8%), and the 2-year overall survival was 59.2% (95% CI, 47.3%-69.3%). The most common toxicities were hematologic and led to treatment discontinuation in 15% of patients. This large prospective and uniform series of AITL treatment data was used to perform an integrative analysis of clinical, pathologic, biologic, and molecular data. TET2, RHOA, DNMT3A, and IDH2 mutations were present in 78%, 54%, 32%, and 22% of patients, respectively. IDH2 mutations were associated with distinct pathologic and clinical features and DNMT3A was associated with shorter PFS. In conclusion, the combination of lenalidomide and CHOP did not improve the CMR in AITL patients. This trial clarified the clinical impact of recurrent mutations in AITL. This trial was registered at www.clincialtrials.gov as #NCT01553786. •Lenalidomide CHOP did not improve the complete metabolic response rate compared with historical controls in previously untreated AITL patients aged 60 to 80 years.•DNMT3A mutations were present in 32% of patients and appeared to confer shorter PFS. [Display omitted]